Fate of cefotaxime-resistant enterobacteriaceae and ESBL-producers over a full-scale wastewater treatment process with UV disinfection - Silva, Isabel (2018)
Disinfection by UV radiation is one of themost promising solutions to reduce the bacterial load and antibiotic resistance in the final effluents of urban wastewater treatment plants (UWTP). Our aim was to evaluate the fate of cefotaxime-resistant Enterobacteriaceae and Extended Spectrum Beta-Lactamase (ESBL) producers in a full-scale system that includes UV-C disinfection. Over treatment, the abundance of cefotaxime-resistant Enterobacteriaceaewas reduced,with reductions of 1.9 log units after secondary treatment (STWsamples) and 1.8 log following UV disinfection (UTW samples). These reductions, did not reflect the variations in the prevalence of cefotaximeresistant Enterobacteriaceae, estimated to be of 3% in rawwastewater (RW), 18% in STWand 3% in UTW. A significant increase of cefotaxime-resistant bacterial counts (0.5 log; p b 0.05)was observed after 3 days of storage. In a total of 1799 cefotaxime-resistant Enterobacteriaceae isolates, 15% harboured blaCTX-M (n = 274), 11% blaTEM (n = 194) and 4% blaSHV (n = 72). While the ESBL gene prevalence decreased over treatment, the prevalence of the intI1 gene decreased after ST but slightly increased in UTW samples. The blaCTX-M-carriers were identified as Escherichia coli and Klebsiella pneumoniae, mostly multi-drug resistant (90.5%) and carrying integrase genes (82.8%). The blaCTX-M gene variants (48 blaCTX-M-15, 9 blaCTX-M-32, 8 blaCTX-M-1, 5 blaCTX-M-27, and 2 blaCTX-M-14) were flanked by ISEcp1, ISEcp1/IS26, IS903 and ORF477 in 8 different arrangements. The IncF plasmid replicon type was highly prevalent among blaCTX-M-carrying Escherichia coli (74.5%) while IncR predominated among K. pneumoniae (54.5%). Our results confirmed the potential of UV-C disinfection to remove antibiotic resistant bacteria. Still, resistant Enterobacteriaceae (about 30 × 106 cells per m3 of water), presenting traits that might potentiate antibiotic resistance spread, are released in the final effluent. In addition, a significant regrowthwas observed after storage. These results suggest that improvements ofwastewater disinfection are still required tominimize the risks associated with UWTP discharges